Affective disorders and self-injurious behavior in children and young adults with carbohydrate metabolism disorders - Niedobylski, Sylwiusz; Michta, Kacper; Próchnicki, Michał (Current Problems of Psychiatry, 2024)
Introduction: Affective disorders and carbohydrate metabolism disorders are problems of increasing importance in the population of children, teenagers and young adults. Much evidence indicates that these problems may co-occur with increased frequency and have much more serious consequences than on their own.Material and methods: Inclusion criteria were established for the review of studies and comprised participants under 25 years of age diagnosed with carbohydrate metabolism disorders, psychometric measurements of symptoms of affective disorders and self-aggressive tendencies. Review of the MEDLINE database was conducted.Discussion: The results of 10 out of 12 studies included in the review indicated significantly increased risk of depression and suicidal tendencies in patients with diabetes. In the described publications, the frequency of affective disorders in a specific population ranged from 1.2% to 47.6% and up to 60.4% for unspecified affective disorder, sub-threshold and fully symptomatic, and the HR ranged from 1.33 to 2.0 for fully symptomatic affective disorders and up to 6.49 for unspecified affective disorder, sub-threshold and fully symptomatic. Descriptions of the incidence of self-injurious behavior and suicidal tendencies estimate them in the range from 0.8% to 35.7%, and in the studies comparing to a control group, the risk for a suicide attempt was between HR: 1.7 and 3.25.Conclusions: The occurrence of affective disorders in children and young adults is significantly more frequent in patients with diabetes compared to patients without carbohydrate metabolism disorders.